Influence of Magnetic Force for Peristaltic Transport of Non-Newtonian Fluid Through Porous Medium in Asymmetric Channel - Nassief, Amaal Mohi; Abdulhadi, Ahmed M. (Iraqi Journal of Science, 2023)
In this paper, we study the effects of a magnetic force on the flow of hybrid bio - nano fluid (Cu - Au. NPs) for a peristaltic channel through a porous medium in an asymmetric channel. Nanoparticles of gold and copper as well as the blood (the base fluid) is taken into account. By using the Adomian decomposition method to solve the governing equations, formulas for velocity, stream function, temperature, current density, and magnetic force have been obtained. The findings show that Gold nanoparticles have an elevation magnetic force compared with copper nanoparticles, based on fluid (blood) and hybrid nanofluid. Finally, the phenomenon of trapping is offered as an explanation for the physical behavior of many parameters. The effect of physical parameters is plotted and analyzed by using the Mathematica software.